ANALISIS PENGARUH FAKTOR RASIO INDEKS LQ45 TERHADAP HARGA INDEKS LQ45 TAHUN 2016-2018 - Julfasmi Hi M. N; Jihan Nurwahidaha; Annisa Noor Hidayat; Edy Widodo (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2021)
Panel data, in some special cases, it is also called cross-sectional time series data or longitudinal data. The LQ45 Index consists of 45 issuers who have passed the Liquidity Selection Process (LiQuid) and several other selection criteria. These criteria may include  market capitalization considerations. This study aims to identify the factors that influence the 2016-2018 LQ45 index. This study uses panel data from 10 companies listed in the LQ45 index from 2016 to 2018 and uses a fixed effects model. Based on the analysis, all independent variables consisting of profit per share (EPS), book price (BV), price-earnings ratio (PER), price-to-book value ratio (DER), price-to-book value ratio (PBV), and price-earnings ratio. Investment (ROA), capital profit margin (ROE), and net profit margin (NPM)  have a significant  effect on the price-earnings ratio of 10 for LQ45 registered companies. However, only the variable book value (BV) and price-to-book value ratio (PBV) that affect the 10 companies listed on LQ45 do not affect the stock prices of the 10 companies listed on LQ45.